2017
DOI: 10.1246/cl.170046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anion in Glyme-based Electrolyte for Li-O2 Batteries: Stability/Solubility of Discharge Intermediate

Abstract: This study demonstrates that the amount of discharge product (Li 2 O 2 ) precipitated on the separator in a lithium oxygen cell using glyme-based electrolytes depends on the anion. The stability of the discharge intermediate (LiO 2 ) in the electrolyte has been shown to depend on the anionic species, which is related to Li 2 O 2 precipitation on the separator. The implications for producing an efficient and long-life Li-O 2 cell are elaborated. Keywords: Li-O 2 battery | Lithium superoxide | AnionThe Li-O 2 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…8e shows how the fraction of Li 2 O 2 in the separator, with reference to the theoretical total amount of Li 2 O 2 , changes with the anion composition. 119…”
Section: “Glyme Electrolyte” In a Li–o2 Battery: The Upcoming Futurementioning
confidence: 99%
See 1 more Smart Citation
“…8e shows how the fraction of Li 2 O 2 in the separator, with reference to the theoretical total amount of Li 2 O 2 , changes with the anion composition. 119…”
Section: “Glyme Electrolyte” In a Li–o2 Battery: The Upcoming Futurementioning
confidence: 99%
“…Notably, this system could store even more energy than the Li–S cell and has been suggested as a possible battery for future applications. 105–130 In this review, we discuss with chronological details various developments in the research on glyme-based electrolytes for lithium batteries, which are summarized in the scheme in Fig. 1 (panel a).…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Therefore, considerable efforts have been placed on attempting to catalyze the charging process in Li-O 2 batteries. While solid-state catalysts have been employed to reduce the overpotential during charge, including metal oxides, 31,32 modified carbon, [33][34][35] and metals or metal alloys, 35,38 these catalysts rely on good electrical contact between Li 2 O 2 and the catalyst throughout the entire charging process, 37 cannot oxidize Li 2 O 2 that forms electronically isolated from the positive electrode, 39 and do not suppress side reactions during charging. 36 An alternative approach is the use of soluble redox mediators to promote electron transfer to the surface of the electronically insulating Li 2 O 2 , 40 where the redox mediator is first electrochemically oxidized at the electrode surface and then the oxidized form of the redox mediator chemically oxidizes Li 2 O 2 to…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive investigations based on both experiments and calculations have shown that the formation of stable solvate cations is responsible for the high thermal and enhanced electrochemical stabilities ,,,. SIL‐based electrolytes have also shown excellent performance in various advanced Li‐based batteries ,…”
Section: Introductionmentioning
confidence: 99%